Arts Teacher Education in Lithuanian University of Educational Sciences - Banevičiūtė, Birutė; Kudinovienė, Jolita (Pedagogika, 2014)
The article analyses arts teacher education in Lithuanian University of Educational Sciences, the only university in Lithuania which prepares teachers of four arts subjects – dance, music, theater and visual arts both on bachelor and master’s level. Analyzing this phenomenon input of Arts Education Department of the university is revealed through scientific and pedagogical activities which are closely connected with arts teacher education programmes implemented by the department. Since 1993 when Arts Education Department was founded it went through various changes which led from general university study subject of Arts education towards six arts teacher preparation programmes: dance pedagogy bachelor, theater and film, pedagogy bachelor, dance education, theater education, visual arts education and music education master. Over 500 arts education teachers graduated from Arts Education Department study programmes in the period of 1997–2013.